Szanse i ograniczenia stosowania strategii CSR w polskich przedsiębiorstwach - Codogni, Iwona (Annales. Etyka w Życiu Gospodarczym, 2012)
The topic of the article is the perspectives of CSR in Polish companies. The article contains the definition of corporate socialresponsibility, the state and dynamics of ethical reporting and the factors that can influence the dynamics of CSR in Poland – bothin a favourable and adverse way.